Nonossifying fibromas of the distal tibia: Possible etiologic relationship to the interosseous membrane. (August 2016) - Muzykewicz, David A.; Goldin, Amanda; Lopreiato, Nicholas; Fields, Katie; Munch, John; Dwek, Jerry; Mubarak, Scott J.
Purpose: Nonossifying fibromas (NOFs) present in a characteristic pattern in the distal tibia. Their predilection to this region and etiology remain imprecisely defined. Methods: We performed a retrospective chart review of patients between January 2003 and March 2014 for distal tibial NOFs. We then reviewed radiographs (XRs), computed tomography (CT), and magnetic resonance imaging (MRI) for specific lesion characteristics. Results: We identified 48 distal tibia NOFs in 47 patients (31 male, 16 female; mean age 12.3 years, range 6.9–17.8). This was the second most common location in our population (30 % of NOFs), behind the distal femur (42 %). Thirty-four lesions had CT and nine had MRI. Thirty-one percent were diagnosed by pathologic fracture. Ninety-six percent of lesions were located characteristically in the distal lateral tibia by plain radiograph, in direct communication with the distal extent of the interosseous membrane on 33 of the 34 (97 %) lesions with CT available for review and all nine (100 %) with MRI. The remaining two lesions occurred directly posterior. Conclusions: The vast majority of distal tibial NOFs occur in a distinct anatomic location at the distal extent of the interosseous membrane, which may have etiologic implications. Level of evidence: IV (case series).